First report of plasmid-mediated fluoroquinolone efflux pump QepA in Escherichia coli clinical isolate ST68, in South America - Rincón, Giovanna (2014)
This is the first report of the presence of qepA1 efflux pump gene in Escherichia coli clinical isolate from Argentina, which was associated to other plasmid-mediated quinolone resistance determinants, such as aac(6′)-Ib-cr and qnrB10 and also quinolone resistance determining regions mutations.